The role of information and experience for households' inflation expectations - Conrad, Christian; Enders, Zeno; Glas, Alexander (Working Papers of the Priority Programme 1859, 2020)
Based on a new survey of German households, we investigate the role of information channels and lifetime experience for households' inflation expectations. We show that the types of information channels that households use to inform themselves about monetary policy are closely related to their socio-economic characteristics. These information channels, in turn, have an important influence on the level of perceived past and expected future inflation, as well as uncertainty thereof. The expected future change of inflation and the unemployment rate, however, is strongly influenced by individual experience of these variables. Similarly, the expected response of inflation to a change in the interest rate is also shaped by experience. We propose the interpretation that households obtain inflation numbers from the media, but their 'economic model' is shaped by experience.
Keywords: Graue Literatur